HDR brachytherapy in vivo source position verification using a 2D diode array: A Monte Carlo study. (1st June 2018) - Poder, Joel; Cutajar, Dean; Guatelli, Susanna; Petasecca, Marco; Howie, Andrew; Bucci, Joseph; Rosenfeld, Anatoly
Abstract: Purpose: This study aims to assess the accuracy of source position verification during high‐dose rate (HDR) prostate brachytherapy using a novel, in‐house developed two‐dimensional (2D) diode array (the Magic Plate), embedded exactly below the patient within a carbon fiber couch. The effect of tissue inhomogeneities on source localization accuracy is examined. Method: Monte Carlo (MC) simulations of 12 source positions from a HDR prostate brachytherapy treatment were performed using the Geant4 toolkit. An Ir‐192 Flexisource (Isodose Control, Veenendaal, the Netherlands) was simulated inside a voxelized patient geometry, and the dose deposited in each detector of the Magic Plate evaluated. The dose deposited in each detector was then used to localize the source position using a proprietary reconstruction algorithm. Results: The accuracy of source position verification using the Magic Plate embedded in the patient couch was found to be affected by the tissue inhomogeneities within the patient, with an average difference of 2.1 ± 0.8 mm ( k  = 1) between the Magic Plate predicted and known source positions. Recalculation of the simulations with all voxels assigned a density of water improved this verification accuracy to within 1 mm. Conclusion: Source position verification using the Magic Plate during a HDR prostate brachytherapy treatment was examined using MC simulations. In a homogenous geometry (water), the Magic Plate was able to localize the source to within 1 mm, however, the verification accuracy was negatively affected by inhomogeneities; this can be corrected for by using density information obtained from CT, making the proposed tool attractive for use as a real‐time in vivo quality assurance (QA) device in HDR brachytherapy for prostate cancer.